Surfactant Protein A and Microbiome Composition in Patients With Atraumatic Intraoral Lesions - Adibi, Shawn; Seferovic, Davor; Tribble, Gena D.; Alcorn, Joseph L.; Fakhouri, Walid D. (Frontiers in Oral Health, 2021)
Abstract Oral ulcers are lesions are that occur due to disruption of epithelial integrity of the mucosa of the oral cavity. Intraoral ulcers are often associated with pain, redness, symptoms of discomfort and blood hemorrhage. The etiology for many oral ulcers is local trauma, systemic health conditions or medication; for other ulcers the cause is less clear. This pilot study aims to evaluate the salivary components and microbiome in patients with atraumatic pre-ulcerous and ulcerous oral lesions compared to control individuals, while considering three common risk factors for atraumatic ulcers, smoking, stress, and gender. This study uses matched age, sex, and ethnicity samples from healthy and oral lesion patients to investigate the changes in salivary surfactant protein A (SP-A) and examines the prevalence and diversity of the salivary oral microflora. The goal is to determine if there are factors in saliva that have the potential to be used as biomarkers for risk of developing atraumatic oral ulcers. Our data show that the average level of SP-A is significantly reduced in female smokers compared to non-smoker healthy females. The average level of SP-A in female oral lesion patients is reduced compared to controls. The microbiome composition is significantly affected by smoking and the level of SP-A. Comparing the control participants and oral lesion patients, there are 27 species of bacteria that are significantly different, and 25 of these bacteria are also significantly affected by smoking and SP-A. Lefse analysis identified five bacteria that may represent potential biomarkers. This preliminary study demonstrates the potential of the oral microbiome to act as a biomarker for oral ulcer risk and infers potential mechanistic links between risk factors and alterations in innate immune mechanisms such as SP-A levels.